THE RELATIONSHIP OF HIGHER-ORDER THINKING TO LINGUISTIC INTELLIGENCE - M. Asholahudin Asholahudin; Uyu Wahyudin; Nurhaedah Gailea (Green Publisher, 2023)
This objective of research is to know the correlation between higher order thinking with linguistic competence. The method of research is used quantitative method with correlational technique. The try out for research instrument on 17 s.d 23 May 2022 with the total number of respondents 542. The result of try out for research instrument showed up the questionnaire of higher order thinking skill about 25 items is all valids, and also the questionnaire of linguistic competence 25 items was all valid. The result of correlation between higher order thinking skill and linguistic competence which is the repondents about 230 repondents showed up that the correlation is medium. It can be concluded that there is significance between higher order thinking skill and linguistic competence, because ? < 0,05 (0,000 < 0,05).